Interpreting Discontinuity in the Late Works of Debussy - Wheeldon, Marianne (Current Musicology, 2004)
Many writers have commented upon formal discontinuity in Debussy’s music. Robert Sherlaw Johnson compares this discontinuity to the collage technique of Messiaen (1975:102-03); Robert Orledge describes it as mosaic construction (1982:170); Roy Howat refers to it as a definable system of block construction (1983:23n6); and Robert P. Morgan terms it additive structure (1991:48). Yet these scholars were not the first to take note of disjunction in Debussy’s compositional style. Decades earlier, another group of musicians similarly drew attention to Debussy’s use of discontinuity. The composers of the Darmstadt avant-garde in the 1950s and 1960s seized upon Debussy’s works to inspire and legitimize their own formal experiments. Pierre Boulez, Herbert Eimert, Dieter Schnebel, and Karlheinz Stockhausen all acknowledged their debt to Debussy with lectures, articles, recordings, and concerts of his compositions. These composers focused on Debussy’s formal innovations in general and championed Debussy’s last orchestral work, the ballet Jeux (1913), in particular. The present article draws upon many of the insights of the Darmstadt composers to help isolate those features of Debussy’s music that promote discontinuity. By revisiting their commentary and incorporating it, whenever feasible, into analyses of Debussy’s works, I hope to achieve two objectives. First, by cultivating an approach that valorizes discontinuity, I aim to flesh out many of the observations and descriptions scholars have made concerning Debussy’s compositional style, a small selection of which was cited in the opening paragraph. These writers all point to a conspicuous feature of Debussy’s music, one that became more pronounced in his final works. While the Darmstadt composers perhaps overemphasized the role of discontinuity with regard to Jeux, Debussy’s subsequent compositions are more in line with their commentary. For example, certain Preludes (1913) and Etudes (1915), the Trois Poemes de Stephane Mallarme (1913), and the central movements of the Cello Sonata (1915) and Violin Sonata (1917) pursue formal discontinuity further, which becomes even more noticeable in the smaller scope and sparser textures of these compositions.